RANCANG BAGUN SISTEM INFORMASI MANAJEMEN PROYEK PADA PT AEON VISION SYNERGY - Julianto, Julianto; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2021)
PT Aeon Vision Synergy is a company engaged in the service sector as a third person in helping to check a project which consists of several types, namely survey links, survey data, and reports generated from survey data. PT Aeon Vision Synergy has problems in the company's control system because the work system is still conventional so that the data stored is lacking accuracy. Therefore, this study conducted the design of building a system for the company. The method used is the SDLC waterfall model which consists of analysis, design, coding and testing. The results of this study are the existence of a project management information system that makes it easier for employees to control projects as well as attendance and payroll.